DIFFUSION OF INNOVATION AND TECHNOLOGY FOR NATIONAL DEVELOPMENT: SCHOOL OF INNOVATION - Hussain, Imran (MATTER: International Journal of Science and Technology, 2017)
India’s future rests on its ability to harness the creative potential of its large young population. In order to foster innovation and creativity, problem and project-based learning (PBL) play an important role. These help to link education to relevant in real-life experience and this connection is crucial for engaging the young minds and increasing their motivation levels. Undertaking innovative experiments, projects and problem solving exercises in multi-disciplinary set up brings joy to learning. The enjoyment factor involved in such engagement enhances young people’s motivation and interest levels, thereby opens doors for flow and creativity. Thus, provision of innovation spaces in schools and colleges, museums and science centers or institutions of non-formal learning, where such activities can be undertaken is recognized to play an important role in fostering creativity and inspiring innovation by young students. This will ultimately lead to developed culture of innovation in the country.